2022
DOI: 10.3389/fimmu.2022.852811
|View full text |Cite
|
Sign up to set email alerts
|

Navigate Towards the Immunotherapy Era: Value of Immune Checkpoint Inhibitors in Non-Small Cell Lung Cancer Patients With Brain Metastases

Abstract: Brain metastases (BMs) in non-small-cell lung cancer (NSCLC) patients are associated with significant morbidity and poor prognosis. Immune checkpoint inhibitors (ICIs) have resulted in a paradigm shift in the management of advanced NSCLC. However, the value of ICIs in NSCLC patients with BMs remains unclear because patients with BMs are routinely excluded in numerous prospective trials on ICIs. Here, starting from the mechanisms of ICIs for BMs, we will reveal the value of ICIs by reviewing the efficacy and ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 136 publications
(124 reference statements)
0
4
0
Order By: Relevance
“…The estimated PFS rate was 59% (95% CI [49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68] in the Sintilimab-IBI305-CT group versus 30% (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39) in the CT alone group at 6 months, and 28% versus 12% (7-20) at 12 months. The prespecified subgroup analysis showed that the HR for PFS favored patients receiving Sintilimab-IBI305-CT over those receiving CT alone across most subgroups, including patients with BM.…”
Section: Activating Mutations and Brain Involvement: Does It Play A R...mentioning
confidence: 99%
See 1 more Smart Citation
“…The estimated PFS rate was 59% (95% CI [49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68] in the Sintilimab-IBI305-CT group versus 30% (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39) in the CT alone group at 6 months, and 28% versus 12% (7-20) at 12 months. The prespecified subgroup analysis showed that the HR for PFS favored patients receiving Sintilimab-IBI305-CT over those receiving CT alone across most subgroups, including patients with BM.…”
Section: Activating Mutations and Brain Involvement: Does It Play A R...mentioning
confidence: 99%
“…It is commonly believed that anti-angiogenic agents limit tumors growth by inhibiting the unregular vasculature of tumors. However, different studies have demonstrated that low dose of antiangiogenic drugs could induce the normalization of abnormal tumor vascularization, decreasing hypoxia induced by tumor and increasing accessibility for immune cells (65,66). Another approach in the management of advanced CNMP is combinations with antiangiogenic drugs.…”
Section: Combinations With Antiangiogenicsmentioning
confidence: 99%
“…Patients with BMs are mostly underrepresented in clinical trials [74] and prospective data regarding their treatment are limited to clinically selected subgroup of patients with asymptomatic and stable BMs, not requiring significative corticosteroid therapy. To provide real-world evidence on the outcome of these patients, an international real-world study evaluated outcomes of patients with NSCLC treated with first-line anti-PD-1 or anti-PD-L1 monotherapy, also including those with active BMs (39.2%), symptomatic BMs (14.3%), or receiving steroids (27.4%) [75].…”
Section: Future Perspective and Ongoing Trialsmentioning
confidence: 99%
“…The conventional view is that anti-tumor drugs are subject to the central nervous system (CNS) barrier (blood-brain barrier/bloodtumor barrier). However, Several studies have shown that novel drugs, such as three generations-targeted drugs and immune checkpoint inhibitors (ICIs), can achieve effective therapeutic concentrations in the CNS (2,3). In addition, Radiation has synergistic effects with the drugs mentioned above (4)(5)(6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%